Pengaruh Komitmen Organisasi dan Kemampuan SDM Terhadap Efektifitas Pelayanan di Rumah Sakit Khusus Jantung Cabang Utama Sumatera Barat - Rahmad, Rahmad (Jurnal Ekonomi, 2013)
The research object is in the Cardiac Hospital Main Brancg Padang of West Sumatra, which aims to examine the effect of HR organizational commitment and ability to service effectiveness. Data processed by multiple linier regressiom analysis note that the value of the regression coeffecient of organizational commitment variables (X1) is aquak to 0,520. Significance value of variable is the organizational structure of 0,000. if the value significant compared to the level of significance use in this study (=0,05) then the value of greater significance than a significant level used (0,000 0,05). This means that there is significant relationship between organizational commitment to effective service in Cardiac Hospital Main Branch Padang West Sumatra. Thus the hypothesis can be accepted at the 95% confidence level. Data processed with multiple linear regression analysis know that the regression coeffecient of the variable HR Capability (X2) is equal to 0,261. Significance value of the variable is the organizational structure of 0,066. If the value is significant compared to the level of significance use in this study (0,10) then the value is greater than the significance level used significantly (0,066 0,10). This means a significant difference between the ability of HR to the effectiveness of services in the Cardiac Hospital Main Branch Padang West Sumatra. Thus the hypothesis can be accepted at the 90% confidence level.